Parents' Experiences and Perspectives Toward Tuberculosis Treatment Success Among Children in Malaysia: A Qualitative Study - Awaluddin, S. Maria; Ismail, Nurhuda; Yasin, Siti Munira; Zakaria, Yuslina; Mohamed Zainudin, Norzila; Kusnin, Faridah; Mohd Yusoff, Mas Ahmad Sherzkawee; Razali, Asmah (Frontiers in Public Health, 2020)
Introduction: The trends of tuberculosis (TB) treatment success rate among children in Malaysia plateaued at 90% from 2014 to 2017. Malaysia sets a higher treatment success target of 95% to be achieved in line with an affordable, accessible and holistic approach in managing TB among children. Objective: This study aims to explore the parents’ experiences and perspectives towards achieving treatment success among children who were diagnosed with TB in two districts in Selangor state, Malaysia. Methods: The study was conducted using phenomenology study design via an in-depth interview of 15 mothers who were purposively sampled from the list of paediatric tuberculosis cases in the MyTB version 2.1 database in Klang and Petaling Districts of Selangor state. R-based qualitative data analysis (RQDA) package of R version 0.2-8 was used to perform the thematic analysis. Results: Two main themes were identified from this study. The first theme was trust towards the healthcare services with the subthemes of acceptance, self-efficacy, holistic care and perceived benefits. The second theme was the motivation to take or continue medication. The subthemes were support from family, healthcare workers’(HCWs) support, the convenience of healthcare services, community support, personal strength and child’s character. Conclusion: TB treatment success for children can be achieved when parents develop trust in healthcare services and have strong motivational factors to remain steadfast in achieving a successful treatment goal. Psychosocial support should be provided to the primary caregiver who faced any difficulty, while good relationships between parents and HCWs should be maintained. These results will inform the TB programme managers to strengthen the holistic approach and identify the motivational factors among parents of children with TB disease.